Accidents involving specialized aircraft in agriculture aerial spraying - Ravelli, Marcelo Boamorte; Zerbato, Cristiano [UNESP]; Oliveira, Mailson Freire de [UNESP]; Correa, Rafael de Graff [UNESP] (Univ Federal Santa Maria, 2017)
The great challenge for the practice of agricultural aviation has been to avoid accidents. Although, there are technological progress and high resources for safety, accidents continue to occur. The objective of this research was to analyze the influence and occurrence of factors in agricultural aviation accidents in Brazil recently. Based on research and technical - scientific papers written by researchers and aviation authorities, recommendations directed towards reducing the risks associated with this aircraft modality are assessed. The main factors responsible for accidents are normally operational errors and maneuvers that cause flight collisions, engine failures and altitude loss. Professional awareness and qualification converge towards the success of the agricultural pilot in the detection of inherent dangers or occasional in the various systems involved.
Keywords: specialized aviation; agricultural aviation; danger; safety; training